Bodily Matters: The Female Dominican Diaspora in Angie Cruz’s Dominicana - Arce Álvarez, María Laura (International Journal of English Studies, 2023)
The aim of this article is to analyze Angie Cruz’s novel Dominicana from a multicultural and gender perspective focusing on how Cruz introduces the female body as a metaphor for the immigrant experience lived by Dominican Women during the 1960s in the United States. Also, this paper studies how the female body becomes a metaphorical border in the diasporic experience for the central character as a way to depict an essentially female in-between-space. Thus, Cruz rewrites and recreates from the female body the diasporic experience of Dominican women immigrants in New York from an intersectional perspective.